2021
DOI: 10.1002/bse.2727
|View full text |Cite
|
Sign up to set email alerts
|

Board gender diversity and carbon emissions: European evidence on curvilinear relationships and critical mass

Abstract: The role of European businesses in addressing environmental issues and climate change has taken center stage with the European Green Deal. With increasing attention to the effect of board gender diversity (BGD) on firms' environmental performance, the question arises whether BGD has any influence on carbon emissions.Based on legitimacy and critical mass theory, this study empirically investigates the impact of BGD on firms' carbon performance (CP), based on total carbon emissions intensity. The paper relies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
177
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(202 citation statements)
references
References 105 publications
(334 reference statements)
21
177
4
Order By: Relevance
“…Previous studies have excessively analyzed the influence of board gender diversity on firm CSR performance and disclosure (Beji et al, 2020;Byron and Post, 2016;Dwekat et al, 2020;Nuber and Velte, 2021). They concluded that the presence of female directors in the boardroom can improve monitoring capacity of the board.…”
Section: Female Board Representation and Corporate Social Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have excessively analyzed the influence of board gender diversity on firm CSR performance and disclosure (Beji et al, 2020;Byron and Post, 2016;Dwekat et al, 2020;Nuber and Velte, 2021). They concluded that the presence of female directors in the boardroom can improve monitoring capacity of the board.…”
Section: Female Board Representation and Corporate Social Responsibilitymentioning
confidence: 99%
“…Several empirical studies have shown an increased interest in analyzing the relationship between board attributes and CSR policies (Gerged, 2021;Karim et al, 2019;Zubeltzu-Jaka et al, 2020;Khan et al, 2021;El-Bassiouny et al, 2020;Nwude and Nwude, 2021;Al Fadli, 2020;Fatma and Chouaibi, 2021;Chintrakarn et al, 2021;Govindan et al, 2021;Beji and al., 2020;Nuber and Velte, 2021;Ardito et al, 2020;Yarram and Adapa, 2021;Barnea and Rubin, 2010;De Villiers et al, 2011;Campanella et al, 2021). However, these studies yielded inconsistent findings (Dwekat et al, 2020;Endrikat et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these arguments, several studies have confirmed the need for representation of at least three women on the board in order for their presence to contribute positively to socially responsible actions [69] such as environmental initiatives and programmes [70]. However, some scholars disagree, reporting that reaching a critical mass of two women is sufficient to reduce GHG emissions [71] and ensure greater environmental innovation [72].…”
Section: Theories Of the Role Of Women On The Board Of Directors And The Influence Of Women On Csrmentioning
confidence: 99%
“…The results for the relationship of interest are also shown. [27,47,85,89] Use of resources [27,71,85] Emissions [19,47,72,85,[90][91][92] Environmental innovation [30,31,93,94] Environmental performance Negative relationship [87] Consumption of water and energy [95] Environmental innovation [28,34,[96][97][98][99][100][101][102][103][104][105][106] Environmental performance No relationship [29] Consumption of energy [27,85] Environmental innovation Source: authors, based on the literature review.…”
Section: Board Gender Diversity and Environmental Performancementioning
confidence: 99%
“…García-Sánchez et al, 2020b;Valls Martínez et al, 2020), of which 9 studies focusing only on European contexts (e.g. Ben Fatma & Chouaibi, 2021; Gangi et al, 2021;Nuber & Velte, 2021). 132 studies analyse the data of only one country; the most considered countries are geographically distributed and include: United States (26 studies), China (15 studies), Australia (12 studies), Spain (11 studies), Malaysia (7 studies), United Kingdom (7 studies), France (7 studies), Bangladesh (6 studies), Pakistan (5 studies), Italy (5 studies), Canada (4 studies).…”
Section: Sample Characteristics (Sample Size Firm Characteristics) and Year And Country Of Analysismentioning
confidence: 99%